Analisis Faktor-Faktor yang Mendorong Generasi Z Memulai Bisnis Sendiri - Marsela Natalie Hutapea; Rizky Idaman Telaumbanua; Rizky Ramadha; Oscar Majeovan Basieta Surbakti; Jonatan Gerald; Austin Beyn Beril Jahran Saragih (CV. Ulil Albab Corp, 2024)
This study aims to analyze the factors that drive Generation Z to start their own businesses. Generation Z, born after 1996, tends to be more interested in creating business opportunities rather than working for established companies. This research uses a quantitative approach with a survey method targeting students in Indonesia. The independent variables in this study include internal factors such as entrepreneurial motivation and risk-taking attitudes, as well as external factors like the influence of technology, social support, and market opportunities. The results of the simple linear regression analysis show that these driving factors have a positive and significant impact on Generation Z's decision to start their own businesses, with an R² value of 39.5%. Family support, peer influence, and access to technology are critical factors that increase the likelihood of Generation Z engaging in entrepreneurship. This study suggests that policymakers and educational institutions should further support the development of entrepreneurship among young generations.